1997
DOI: 10.1029/96jb03386
|View full text |Cite
|
Sign up to set email alerts
|

Seismic moment‐frequency relation for shallow earthquakes: Regional comparison

Abstract: We test the hypothesis that no statistically significant variation in Mxg occurs in subduction and continent collision zones; the hypothesis cannot be rejected with available data. For the midocean ridges, the Mxg estimate cannot be unambiguously determined; it is quite possible that the estimate is significantly biased because only a small part of tectonic deformation at the ridges is released by earthquakes. These results have importance in evaluating seismic risk and may also lead to developing a physical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
199
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(220 citation statements)
references
References 37 publications
20
199
1
Order By: Relevance
“…In a recent analysis, Bird et al (2000) explain the difference of b-value found earlier (Okal and Romanovicz, 1994;Kagan, 1997Kagan, , 1999 and confirmed here, on the basis that an effective larger b-value will be found when mixing power law distribution with different "corner" magnitudes. Indeed, a similar effect has been shown to increase the b-value in a population of faults with a continuous power law distribution of lengths (Sornette et al, 1991;Lomnitz-Adler, 1992).…”
Section: Estimation Of the Gpd-parameterssupporting
confidence: 86%
See 2 more Smart Citations
“…In a recent analysis, Bird et al (2000) explain the difference of b-value found earlier (Okal and Romanovicz, 1994;Kagan, 1997Kagan, , 1999 and confirmed here, on the basis that an effective larger b-value will be found when mixing power law distribution with different "corner" magnitudes. Indeed, a similar effect has been shown to increase the b-value in a population of faults with a continuous power law distribution of lengths (Sornette et al, 1991;Lomnitz-Adler, 1992).…”
Section: Estimation Of the Gpd-parameterssupporting
confidence: 86%
“…The statistical technique presented here is illustrated using the well-known seismological problem of earthquake energy distribution. A new evidence of spatial homogeneity of shallow earthquake distributions in subduction zones is demonstrated and confirm known results in this domain [Gutenberg and Richter, 1954;Main and Burton, 1984;Main, 1992Main, , 1996Cornell, 1994;Sornette and Sornette, 1999;Kagan, 1994Kagan, , 1997Kagan, , 1999Romanowicz and Rundle, 1993;Romanowicz, 1994;Okal and Romanowicz, 1994;Pacheco and Sykes, 1992;Scholz, 1994aScholz, , 1994b. We confirm that the b-value is very different (b=1.50±0.09) in mid-ocean ridges compared to other zones (b=1.00±0.05) with a very high statistical confidence and propose a physical mechanism contrasting "crack-type" rupture with "dislocation-type" behavior.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…where the exponent b is related to the b-value of the G-R distribution according to b=(3/2) b ( Kagan, 1997Kagan, , 1999). An example of a modified G-R distribution is plotted in Figure 3 for M t =7.0 and M c =9.0 (dashed line) along with a the cumulative distribution of 100 random samples taken from Equation (10) (medium solid line).…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…However, seismicity has only been recorded over a time period which is small compared to the typical average recurrence times of the largest earthquakes which dominate both the total seismic moment release and the damage. The earthquake frequency-magnitude distribution for such rare, damaging earthquakes can be constrained to some extent by the local seismic moment release rate, increasingly available at higher resolution from geodetic data from ground-based and satellite geodesy [Kagan, 1991[Kagan, , 1997Main, 1996]. However, the moment release rate itself does not specify the type of distribution, only the parameters for a given distribution.…”
Section: Introductionmentioning
confidence: 99%